The relationship between different measures of fear learning following tests for reinstatement and spontaneous recovery of extinguished conditioned fear - Neumann, D.; Lipp, Ottmar; McHugh, M. (Nova Science Publishers, Inc., 2012)
Exposure therapy, which is based on extinction in Pavlovian conditioning, is effective in the treatment of anxiety disorders. However, a return of fear (relapse) can occur after treatment. Reinstatement and spontaneous recovery provide two explanations for return of fear. These mechanisms can be difficult to investigate in real-world clinical contexts for practical or ethical reasons. The present research used a laboratory-based fear learning task to examine reinstatement and spontaneous recovery using different measures of fear learning. A differential fear conditioning procedure was used. In acquisition, one conditional stimulus (CS+) was paired with a shock unconditional stimulus (US) and a CS- was presented alone. Both CS+ and CS- were presented alone during extinction. Presentations of the US (reinstatement) or a time delay (spontaneous recovery) were given prior to test trials. During test, shock expectancy was greater for CS+ than CS- for reinstatement and was non-differential, although higher than at the end of extinction, for spontaneous recovery. The CS+ was rated as more unpleasant, more arousing, and more dominating than the CS- for both procedures. Skin conductance responses did not differ between the CS+ and CS-. The results show dissociations between the measures that may reflect differential sensitivity to the learning processes that underlie the return of fear. The application of the results for understanding the possible mechanisms for relapse following exposure therapy for anxiety disorders is discussed. © 2012 by Nova Science Publishers, Inc. All rights reserved.